Control of three-phase induction motor using input-output linearization method - Huynh , Thanh Tường; Bui , Thanh Hiếu; Duong , Hoài Nghĩa (Journal of Technical Education Science, 2016)
Three-phase induction motor is the main equipment in AC drives because of the advantages such as simple structure, solid, reliable operation, low maintenance repairs, low-cost, high performance.... However, the control of induction motor is a difficult and complicated problem because of its strong nonlinearity. This paper applies the feedback linearization control technique (FLC) and the pole assigment method to design a speed and flux controller for induction motors. The torque and the flux are estimated from measurement of voltages and currents of the motor. The comparative study of the motors components (flux, speed, torque, three-phase current) of the proposed method (FLC) with FOC method is conducted. The comparison is done when changing the load on the motor shaft, tracking capability of speed and a sensitivity to changes in operating conditions. Flux and the torque is estimated from the value of the motor current and voltage. The simulation results showed the effectiveness of the proposed method.